ANALYSIS OF CULTURAL INTELLIGENCE (CQ) IN THE UNITED ARAB EMIRATES ECONOMIC DIPLOMACY - Fauzi, Muhammad; Rahayu, Dini Septyana (Mediasi Journal of International Relations, 2024)
This research focuses on using the concept of Cultural Intelligence (CQ) as an analytical lens to identify the economic diplomacy strategy of the United Arab Emirates (UAE). The research method applied is a descriptive qualitative method with data collection techniques involving various sources, including reports, journals, news, and literature related to this topic. Cultural Intelligence is applied through four main dimensions: Motivational CQ, Cognitive CQ, Metacognitive CQ, and Behavioral CQ. This research explores how the UAE, as a multicultural country, utilizes cultural intelligence to shape and implement strategies in its economic diplomacy. The results show that Cultural Intelligence (CQ) is able to act as a lens that enables the identification of a country's economic diplomacy strategy. The high Motivational CQ is reflected in the UAE's enthusiasm to adapt to a dynamic economic environment. Cognitive CQ is applied in managing a positive image and reducing negative stereotypes, increasing attractiveness for expatriates and international economic actors. Meanwhile, Metacognitive CQ is reflected in the UAE's efforts to position themselves as a moderate and tolerant country, creating strong relationships in the Islamic world while still maintaining their cultural identity. Behavioral CQ strategies are manifested in inclusive and responsive policies to cultural conflicts, which strengthen economic relations and reduce uncertainty. This research contributes to the understanding of the role of Cultural Intelligence as an analytical lens in exploring a country's economic diplomacy strategy, particularly in the UAE context. The implications of this research can serve as a basis for the development of better policies and practices in enhancing economic cooperation and achieving national and global goals.